“A gente não quer só comida” : democracia e políticas culturais em Minas Gerais (2001-2011) - Weslaine Wellida Gomes (2014)
This dissertation has as its objective to comprehend some transformations in cultural public policies of Minas Gerais between 2001 and 2011, from a democratic point of view. In the last decade, Brazil has been through important modifications in the cultural field’s public policy management. Out of all these changes, we can mention, in the federal scope, the elaboration and approvement of the National Culture System and National Culture Plan. Also worth mentioning is the creation of new instruments of social participation in the elaboration of policies and the attempt to improve those that already exist as well. Minas Gerais is included in this wide context of discussions of the democratization of cultural policies. That being established, the comprehension of if there has been a process of democratization of these policies in the state is targeted. To answer this issue, this study has been based on three central dimensions of democratization: the principle of equality (expressed through the rights of cultural citizenship); the principle of of political participation (linked to the rights of cultural citizenship), and the decentralization of political power (related to the deconstruction of political power). Empirically, we analyzed the data concerning the state law of Cultural encouragement of Minas Gerais, from 2001 to 2011, and interviews held with public managers and the organized civil society. Despite some advances in these three democratic dimensions, the predominant scenario is of: an expressive concentration of tools from incentive laws; insufficient mecanisms and forms of participation to include the different cultural segments; and the centralization of political decisions. Therefore, we have very effective obstacles for the promotion of equality, participation and decentralization.